1985
DOI: 10.1017/s0033583500005151
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence, haem-iron co-ordination geometry and functional properties of mitochondrial and bacterial c-type cytochromes

Abstract: Cytochromes are found in all biological oxidation Systems which involve transport of reducing equivalents through organized chains of membrane bound intermediates, regardless of the ultimate oxidant (Keilin, 1966; Bartsch, 1978; Meyer & Kamen, 1982). Thus, cytochromes are present not only in the aerobic mitochondrial and bac-terial respiratory chain, but are also found in much more diversified procariotic Systems, including all varieties of facultative anaerobes (nitrate and nitrite reducers), obligate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 70 publications
7
85
0
1
Order By: Relevance
“…78 This effect has been shown to produce a readily identifiable pattern of upfield chemical shifts for the axial Met in reduced cyt c's. 79,80 In both Ht-cyt c 552 variants in this study, the Ala61 -CH 3 is shifted upfield as expected if its position is similar to the -CH 2 in Met61 in the native Ht-cyt c 552 (δ ≈ 1.5 ppm; Table 2). In the case of an Asn64 (or Gln64) side-chain NH 2 proton, location above the center of the heme macrocycle (i.e., in position to interact with an axial ligand) would mean a significantly lower chemical shift from the expected value of ∼6-8 ppm ("randomcoil" chemical shifts are 6.8 and 7.6 ppm 55 ).…”
Section: C(t)supporting
confidence: 79%
“…78 This effect has been shown to produce a readily identifiable pattern of upfield chemical shifts for the axial Met in reduced cyt c's. 79,80 In both Ht-cyt c 552 variants in this study, the Ala61 -CH 3 is shifted upfield as expected if its position is similar to the -CH 2 in Met61 in the native Ht-cyt c 552 (δ ≈ 1.5 ppm; Table 2). In the case of an Asn64 (or Gln64) side-chain NH 2 proton, location above the center of the heme macrocycle (i.e., in position to interact with an axial ligand) would mean a significantly lower chemical shift from the expected value of ∼6-8 ppm ("randomcoil" chemical shifts are 6.8 and 7.6 ppm 55 ).…”
Section: C(t)supporting
confidence: 79%
“…'H-NMR studies of D. vulgaris Hildenborough and D. desulfuricans Norway cytochromes cSs3 have demonstrated that the coordination geometry at the heme iron differs depending on its oxido-reduction state. In the oxidized protein the heme iron has the same coordination geometry as in the eukaryotic cytochromes (R chirality), whereas in the reduced form a new coordination geometry was observed, similar to that in cytochrome css, from Pseudomonas or Rhodopseudomonas gelutinosa and cytochrome c5 from Pseudornonas mendocina (S chirality) [7]. This atypCorrespondence to F. Guerlesquin, Laboratoire de Chimie Bacterienne, CNRS, 31 Chemin Joseph Aiguier, BP71, F-13277 Marseille, France…”
mentioning
confidence: 60%
“…The conformation of the methionine-80 side chain relative to the heme determines the distribution of electron spin density on the heme. It has been speculated that the interaction with a redox partner could trigger a rearrangement of the relative positions of heme and methionine-80 axial ligand and thus of the distribution of electron spin density, thereby facilitating electron transfer (36). Indeed, NMR studies on cytochrome c complexed to various electron donors and acceptors do show such a redistribution of spin density (37).…”
Section: Resultsmentioning
confidence: 99%